2004
DOI: 10.1109/tdmr.2004.831990
|View full text |Cite
|
Sign up to set email alerts
|

Interface Reliability Assessments for Copper/Low-k Products

Abstract: Multiple new materials are being adopted by the semiconductor industry at a rapid rate for both semiconductor devices and packages. These advances are driving significant investigation into the impact of these materials on device and package reliability. Active investigation is focused on the impact of back-end-of-line (BEOL) processing on Cu/low-k reliability. This paper discusses Cu/low-k BEOL interfacial reliability issues and relates key items from the assembly process and packaging viewpoint that should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…From the experimental results, since the thermal expansion coefficients of different materials induce the interfacial stress mismatch between different layers, layer stacking order can affect the interfacial adhesion strength significantly. A welldesigned layer stacking order for a multilayer structure can minimize the extrinsic stress of mismatch, which can further increase the interfacial adhesion strength [23].…”
Section: B Investigation Of the Effects Of Adding Adhesion Layer Mementioning
confidence: 99%
“…From the experimental results, since the thermal expansion coefficients of different materials induce the interfacial stress mismatch between different layers, layer stacking order can affect the interfacial adhesion strength significantly. A welldesigned layer stacking order for a multilayer structure can minimize the extrinsic stress of mismatch, which can further increase the interfacial adhesion strength [23].…”
Section: B Investigation Of the Effects Of Adding Adhesion Layer Mementioning
confidence: 99%
“…Although the numerical analysis is continuum-based, this observation nevertheless implies the concentration of crystal defects, namely dislocations and vacancies, near these locations and can promote subsequent void nucleation and electromigration damages. Experiments have shown that the interface between Cu and the adjacent barrier layers is an easy diffusion path and is particular prone to failure initiation [234,[289][290][291][292][293]. The adhesion quality of the interface in actual devices plays a very important role.…”
Section: Passivated Single-level Cu Linesmentioning
confidence: 99%
“…These methods are limited by the intricate sample preparation and the bonding process, which can cause undesirable compositional changes in many films. Moreover, in some thin film systems, it is difficult to introduce a pre-crack and grow the crack in a controlled manner along the interface of interest (Hartfield et al, 2004).…”
Section: Introductionmentioning
confidence: 99%